Mid- to long-term periprosthetic bone density changes after cementless short stem hip arthroplasty in elderly: A clinical and radiological analysis - Brandl, Max; Jahnke, Alexander; Fölsch, Christian; Rickert, Markus; Ishaque, Bernd Alexander; Justus Liebig University Giessen (My University, 2024)
Introduction: Short stem prostheses were originally designed for younger and more active patients. In recent years, they have been increasingly offered to older patients. This study evaluates the mid-to long-term survival of a short stem prosthesis and the changes in periprosthetic bone density following implantation of a cementless short hip stem in patients over 60 years of age. Methods: 118 patients aged over 60 received short stem prostheses. Clinical examination included Harris Hip Score (HHS) and Hip Disability and Osteoarthritis Outcome Score (HOOS). 93 patients were followed clinically for at least five years. 53 patients underwent dual-energy x-ray absorptiometry (DXA) and radiographic evaluation. Follow-up intervals were preoperative and postoperative (t0), at approximately six months (t1), at approximately two years (t2), and at approximately five years or later (t3). Results: Over a mean 6.7-year observation period for all 118 patients, one stem revision occurred due to a traumatic periprosthetic stem fracture. The five-year survival rate for the endpoint survival of the Metha® stem in 95 at-risk patients is 99.2%. HHS improved significantly from t0 55.3 ± 11.5 (range 30–79) to t3 95.3 ± 8.6 (range 57–100) at a mean of 8.0 years (p < 0.001). HOOS improved significantly in each subscale (p < 0.001). Bone mineral density (BMD) was available for review in 53 patients after a mean of 7.1 years. BMD increased from t0 to t3 in region of interest (ROI) 3 (+0.4%) and ROI 6 (+2.9%) and decreased in ROI 1 (−10.3%), ROI 2 (−9.8%), ROI 4 (−5.3%), ROI 5 (−3.4%) and ROI 7 (−23.1%). Conclusions: The evaluated short stem prosthesis shows a remarkably high survival rate in elderly patients, accompanied by excellent clinical results. Load transfer measurements show a metaphyseal-diaphyseal pattern with a trend towards increased diaphyseal transfer over the period observed.
Keywords: ddc:610